Digest of Papers. 2005 Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2005.
DOI: 10.1109/smic.2005.1587901
|View full text |Cite
|
Sign up to set email alerts
|

High-resistivity silicon surface passivation for the thin-film MCM-D technology

Abstract: High-resistivity silicon (HRSi) has excellent properties as substrate material to integrate microwave passive components. However, the existence of a layer of free surface charges under the silicon-silicon dioxide interface generated by impurities in the SiO 2 and in the interface itself undermines the RF properties of the bulk HRSi. This paper demonstrates how the surface charges increase the RF loss of CPW lines processed on HRSi and make their loss DC dependent. It also presents how Ar implantation can succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although attenuation of the unimplanted CPW line was stable after high temperature annealing, a large dc-voltage dependence was observed (not shown) [8]. For a p-type Si substrate, a positive bias voltage leads to an inversion layer underneath the interface of a MOS structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although attenuation of the unimplanted CPW line was stable after high temperature annealing, a large dc-voltage dependence was observed (not shown) [8]. For a p-type Si substrate, a positive bias voltage leads to an inversion layer underneath the interface of a MOS structure.…”
Section: Resultsmentioning
confidence: 97%
“…The attenuation of the unimplanted CPW line (sample A) was about 1.7 dB/cm at 30 GHz while those of the implanted CPW lines (samples B, E) were about 0.7 dB/cm at 30 GHz. The silicon substrates were damaged by ion implantation, thus generating traps [8]. These traps capture mobile carriers near the surface of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this technique eliminates the additional loss introduced by the charges [5], [6]. The authors have previously demonstrated that the surface of the HRSi remains passivated after the thin-film processing [7], [8] and therefore it is the passivation technique used in the wafers subject of this study. Fig.…”
Section: Technology Descriptionmentioning
confidence: 94%